2017
DOI: 10.1016/j.jebo.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Culture, compliance, and confidentiality: Taxpayer behavior in the United States and Italy

Abstract: l o n g w i t h i n f o r m a t i o n o n t h e e x t e n t o f t h e i r n o n c o m p l i a n c e) a n d o f " F u l l C o n f i d e n t i a l i t y " (e. g. , n o p u b l i c d i s s e m i n a t i o n o f p h o t o s o r n o n c o m p l i a n c e) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
1
13
0
3
Order By: Relevance
“…However, the inter-play between cultural and institutional aspects remain underexplored (Alesina and Giuliano 2015;Guiso et al 2006;Hodgson 2006), particularly regarding the role of culture on individuals' attitudes towards rent-seeking behaviour and compliance with the law (Alm et al 2017;Hodgson and Jiang 2007). We aim to bridge this gap by investigating the relationship between individual-level cultural value orientation and tax morale, commonly defined as intrinsic non-pecuniary motivations towards tax compliance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inter-play between cultural and institutional aspects remain underexplored (Alesina and Giuliano 2015;Guiso et al 2006;Hodgson 2006), particularly regarding the role of culture on individuals' attitudes towards rent-seeking behaviour and compliance with the law (Alm et al 2017;Hodgson and Jiang 2007). We aim to bridge this gap by investigating the relationship between individual-level cultural value orientation and tax morale, commonly defined as intrinsic non-pecuniary motivations towards tax compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Fortin et al (2007) and Coricelli et al (2010) find similar results in tax evasion games without the inclusion of a public good, and Coricelli et al additionally show that cheating was accompanied by emotional arousal under the threat of shaming. Alm et al (2017) distinguish between the decisions to participate in tax evasion and between the amount evaded. They find that shaming foremost deterred participation in tax evasion and that shaming worked regardless of differing social norms on compliance.…”
Section: Related Literaturementioning
confidence: 99%
“…The results of our experiment have shown that, besides the amount contributed to the public good, disclosure is also connected to the likelihood of being fully compliant or not (see Table 4). This is understandable, since full compliance is tantamount to keeping an untarnished reputation, and the decision on how much tax to pay could be predated by a binary decision whether to avoid or not (see Alm et al, 2017 for a related approach). In the Supplementary Material, we report results from nonlinear probit regressions on the likelihood of being fully compliant.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Lewis et al (2009) indicate British subjects were more compliant; Zhang et al (2016) present compelling evidence suggesting Italians are more compliant than Brits; and Andrighetto et al (2016) unearths that on average Swedes are not more compliant than Italians, but the behaviors between the countries do differ, in that, Italians are more likely to fudge than Swedes. Most recently, Alm et al (2017) were interested in differences in tax compliance behavior in Italy and the United States with respect to public disclosure. Due to the relative similarity of the tax systems, but the large variation in tax behavior, and the somewhat ambiguous cross-national results between Italy, the United States, and other European countries, tax compliance experiments in which we leverage real world institutions in the United States and Italy can provide a fruitful comparison.…”
Section: Country Selectionmentioning
confidence: 99%
“…Indeed, the fight against tax evasion is a common theme among Italian politicians and citizens (D'Attoma 2017). It is also referenced as the cause of many societal problems such as reductions in public spending and inequality (Alm et al 2017;Santoro and Fiorio 2010).…”
Section: Country Selectionmentioning
confidence: 99%